Evaluation of scientific complementary metal–oxide–semiconductor sensors for sky survey applications. Issue 7 (30th October 2019) - Karpov, Sergey; Bajat, Armelle; Christov, Asen; Prouza, Michael
Abstract: Scientific complementary metal–oxide–semiconductor (CMOS) image sensors are a modern alternative for typical charge‐coupled device detectors, as they offer low read‐out noise, large sensitive area, and high frame rates. All these make them promising devices for a modern wide‐field sky surveys. However, the peculiarities of CMOS technology have to be properly taken into account when analyzing the data. In order to characterize these, we performed extensive laboratory testing of Andor Marana scientific CMOS (sCMOS) camera. Here, we report its results, especially on the temporal stability and linearity, and compare it with the previous versions of Andor sCMOS cameras. We also present the results of an on‐sky testing of this sensor connected to a wide‐field lens and discuss its applications for astronomical sky surveys.